Moral circle expansion: A promising strategy to impact the far future. (June 2021) - Anthis, Jacy Reese; Paez, Eze
Highlights: We need strategies to reduce existential risks, particularly suffering risks related to artificial intelligence. Moral exclusion seems to be a key contributor to historical atrocities and present and future existential risks. Moral circle expansion is a tractable project, as evidenced by history, economics, sociology, and psychology. Moral circle expansion is a promising strategy to impact the far future. Two particularly important future frontiers of the moral circle are wild animals and sentient artificial intelligence. Abstract: Many sentient beings suffer serious harms due to a lack of moral consideration. Importantly, such harms could also occur to a potentially astronomical number of morally considerable future beings. This paper argues that, to prevent such existential risks, we should prioritise the strategy of expanding humanity's moral circle to include, ideally, all sentient beings. We present empirical evidence that, at micro- and macro-levels of society, increased concern for members of some outlying groups facilitates concern for others. We argue that the perspective of moral circle expansion can reveal and clarify important issues in futures studies, particularly regarding animal ethics and artificial intelligence. While the case for moral circle expansion does not hinge on specific moral criteria, we focus on sentience as the most recommendable policy when deciding, as we do, under moral uncertainty. We also address various nuances of adjusting the moral circle, such as the risk of over-expansion.